Intermittent sacral neuromodulation for idiopathic urgency urinary incontinence in women. Issue 2 (3rd December 2015) - ′t Hoen, Lisette A.; Groen, Jan; Scheepe, Jeroen R.; Blok, Bertil F.M.
Abstract : Aims: SNM has been proven to be effective in the treatment of refractory UUI. Total costs and patient burden due to regular battery changes may prevent broad implementation of this treatment. The aim was to achieve a minimal improvement of 50% in incontinence episodes compared to pre‐SNM by using iSNM. Methods: This prospective cohort study was performed in women with UUI receiving treatment with SNM for a minimum of 6 months. The neurostimulator was programmed to 8 hr "on" and 16 hr "off" per day for 12 weeks. Prior to iSNM, data were collected during no SNM and cSNM. Bladder diaries and various patient reported outcome measures were collected at predetermined time points: 1–5 weeks, and 8, 12, and 16 weeks. Nonparametric tests were used for the statistical analysis. Results: Of the 19 patients 63% showed an improvement of >50% of incontinence episodes during iSNM compared to pre‐SNM. Bladder diary parameters showed a difference between pre‐SNM and iSNM median ( P ‐value); incontinence episodes/24 hr, 4.1–1.0 ( P = 0.04), incontinence severity, 2.0–1.0 ( P = 0.001), voiding episodes/24 hr, 13.0–8.0 ( P = 0.001), and voided volume, 149–219 ml ( P = 0.04). The UDI‐6, 50.0–27.8 ( P = 0.03), and the IIQ‐7 scores, 50.0–9.5 ( P = 0.04) also showed a significant improvement. No difference was demonstrated between iSNM and cSNM. Conclusions: Compared to pre‐SNM parameters, iSNM shows an improvement in both objective and subjective outcomes. Specifically no difference was found between iSNM and cSNM, indicating that iSNM could be a feasible and cost‐effective alternative. Neurourol. Urodynam. 36:385–389, 2017 . © 2015 Wiley Periodicals, Inc.